The factoring of the expression x²=-x+6 is (x-2)(x+3)
By ordering the values, we get:
x² + x - 6 = 0
To solve this exercise, we have to follow the rules of factoring:
1. Looking for the a and b number that state the following equations:
Analyzing that (a*b) is a negative number, it means that (a) and (b) have different signs, and due to the results of (a+b) is positive the higher number has to be the positive one.
The number could be:
a = -2
b = 3
Confirming:
a + b = -2 + 3 = 1
a * b = (-2) * 3 = - 6
2. Rewriting the factored expression (x+a)(x+b) with the obtained values, we get:
(x-2)(x+3)
<h3>What is factoring?</h3>
Is a technique that consist of decomposition of a factor into a product of another factor, which when multiplied together give the original number.
Learn more about factoring at brainly.com/question/24734894
#SPJ4
The answer to your problem is
Answer:
105 cm squared
First find the area of the rectangle
length x width = area
6 x 15 =90
Now find area of triangle
subtract 11-6 and 15-9 to get the dimensions for the triangle
5 and 6 are the dimensions
Length x height / 2 = area of triangle
5 x 6 = 30
30 / 2 = 15
add the areas together
90 + 15 = 105
105 cm squared
hope this helps
Step-by-step explanation:
Um...thats a tough one... well first you have to put the formula together which is pi(10)(26)+pi(10)^2 multiply 10 times 26 then 10 times ten giving us a much more easier equation 260pi + 100pi. we can cross off answer A and answer C just by looking at the simplified equation. now add the two together, giving us 360pi inches^2